2004
DOI: 10.1080/02652040310001637811
|View full text |Cite
|
Sign up to set email alerts
|

Fluconazole encapsulation in PLGA microspheres by spray-drying

Abstract: Fluconazole-loaded PLGA microspheres were prepared by the spray-drying process. The influence of some process parameters on the physical characteristics of the microspheres was evaluated. Neither type nor polymer concentration influenced significantly the mean diameter of the microspheres, their size distribution and encapsulation efficiency of the drug. However, the drug loading greatly affected their size and the physical state in which fluconazole can exist in the matrix of the carriers, and, thus, affected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 10 publications
1
20
0
2
Order By: Relevance
“…These results are in good agreement with a previous report that at low nominal drug loading, fluconazole was incorporated in an amorphous state or in a molecular dispersion in the microsphere matrix, but at high nominal drug loading, part of the drug was in a crystalline form. 27 LeCorre et al 26 have also observed relatively highly loaded drug existing in a particulate dispersion instead of a molecular dispersion.…”
Section: Influence Of Drug Loading On Microsphere Propertiesmentioning
confidence: 95%
“…These results are in good agreement with a previous report that at low nominal drug loading, fluconazole was incorporated in an amorphous state or in a molecular dispersion in the microsphere matrix, but at high nominal drug loading, part of the drug was in a crystalline form. 27 LeCorre et al 26 have also observed relatively highly loaded drug existing in a particulate dispersion instead of a molecular dispersion.…”
Section: Influence Of Drug Loading On Microsphere Propertiesmentioning
confidence: 95%
“…Pure water is then added to allow the solvent to diffuse into the aqueous phase leading to the formation of particles. This method allows for better control of the particle size, by controlling the stabilizer concentration, the stirring rate and the polymer concentration [22,23]. However, an additional purification step is necessary to remove the electrolyte used for the saturation of the aqueous phase.…”
Section: Preparation Of Pla/plga Particlesmentioning
confidence: 99%
“…Many approaches are proposed for the preparation of PLGA particles. The emulsification-evaporation method [64][65][66][67], spontaneous emulsificationsolvent diffusion method (SESD) [20,68], nanoprecipitation method [69,70] and spray-drying [71][72][73] are all widely used in preparing PLGA particles of various sizes. Each of these methods employs a similar first step, where an aqueous drug solution is emulsified in an organic polymer solution to form a water-in-oil dispersion (W 1 /O).…”
Section: Formulation Aspects Of Micro and Nano Po-lymeric Particlesmentioning
confidence: 99%